Review: Development and Technical Design of Tangible User Interfaces in Wide-Field Areas of Application - Krestanova, Alice; Cerny, Martin; Augustynek, Martin (Sensors (Basel, Switzerland), 2021)
A tangible user interface or TUI connects physical objects and digital interfaces. It is more interactive and interesting for users than a classic graphic user interface. This article presents a descriptive overview of TUI's real-world applications sorted into ten main application areas-teaching of traditional subjects, medicine and psychology, programming, database development, music and arts, modeling of 3D objects, modeling in architecture, literature and storytelling, adjustable TUI solutions, and commercial TUI smart toys. The paper focuses on TUI's technical solutions and a description of technical constructions that influences the applicability of TUIs in the real world. Based on the review, the technical concept was divided into two main approaches: the sensory technical concept and technology based on a computer vision algorithm. The sensory technical concept is processed to use wireless technology, sensors, and feedback possibilities in TUI applications. The image processing approach is processed to a marker and markerless approach for object recognition, the use of cameras, and the use of computer vision platforms for TUI applications.
Keywords: education; sensors; lidé; smart object; hra a hračky; uživatelské rozhraní počítače; User-Computer Interface; tangible user interface; augmented reality; tangible; Play and Playthings; Humans